Jogging and practical-duration foam-rolling exercises and range of motion, proprioception, and vertical jump in athletes - Romero-Franco, N.; Romero-Franco, J.; Jiménez-Reyes, P. (Journal of Athletic Training, 2019)
Context: Foam-rolling exercises are frequently included in warmups due to their benefits for increasing range of motion (ROM). However, their effects on proprioception and vertical jump have not been analyzed and therefore remain unclear. Moreover, the effects of performing practical-duration foam-rolling exercises after typical warmup exercises such as jogging are unknown.